2020
DOI: 10.1126/scitranslmed.aaz8664
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-engineered human brown-like adipocytes prevent diet-induced obesity and ameliorate metabolic syndrome in mice

Abstract: Brown and brown-like beige/brite adipocytes dissipate energy and have been proposed as therapeutic targets to combat metabolic disorders. However, the therapeutic effects of cell-based therapy in humans remain unclear. Here, we created human brown-like (HUMBLE) cells by engineering human white preadipocytes using CRISPR-Cas9–SAM–gRNA to activate endogenous uncoupling protein 1 expression. Obese mice that received HUMBLE cell transplants showed a sustained improvement in glucose tolerance and insulin sensitivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
98
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(102 citation statements)
references
References 69 publications
3
98
0
1
Order By: Relevance
“…Overall, this study provides direct evidence that Ang II-induced hypertension is associated with BAT deficiency. The latest study demonstrated that transplantation of engineered human brown-like adipocytes prevents diet-induced obesity, ameliorates metabolic syndrome, and activates endogenous brown fat in mice [27]. This novel study provides a potential strategy to combat metabolic syndrome by using engineered Fig.…”
Section: Discussionmentioning
confidence: 88%
“…Overall, this study provides direct evidence that Ang II-induced hypertension is associated with BAT deficiency. The latest study demonstrated that transplantation of engineered human brown-like adipocytes prevents diet-induced obesity, ameliorates metabolic syndrome, and activates endogenous brown fat in mice [27]. This novel study provides a potential strategy to combat metabolic syndrome by using engineered Fig.…”
Section: Discussionmentioning
confidence: 88%
“…3D adipospheres and human adipose tissue were fixed and stained for lipid droplets (red) and proteins of the extra cellular matrix indicated engineering hiPSCs-derived adipocytes to maintain UCP1 expression. Very interestingly, Yu-Hua Tseng's group has recently reported the possibility to activate endogenous UCP1 expression in immortalized white preadipocytes (HUMBLE cells) through clustered regularly interspaced short palindromic repeat-associated Cas9 (CRISPR/Cas9) technology [51]. In contrast to primary adipose progenitors, CRISPR-mediated genome editing of hiPSCs is practicable [52].…”
Section: Future Perspectives For Bat and Ipsc-derived Adipocyte Transmentioning
confidence: 99%
“…The recruitment of brown adipocytes has been suggested as a therapy to restore the metabolic balance of WAT and ameliorate insulin resistance [ 81 ]. Indeed, the transplantation of CRISPR-engineered UCP-1 expressing adipocytes in obese mice restores both the glucose tolerance and the insulin sensitivity, thus reverting the obesity-associated phenotype [ 82 ]. Other strategies have been proposed to increase the browning of WAT, such as the deacetylation of PPAR-γ [ 83 ] or the ablation of the macrophage IRE1α pathway [ 84 ].…”
Section: Molecular Alterations In Obesity and Bcmentioning
confidence: 99%